(untitled) (Research, Society and Development, 2022)
The Real Estate Transfer Tax (ITBI) is a tax that is the responsibility of the municipalities. The calculation of the tax is made from the calculation basis (venal value) and a rate. It is common to witness some administrative bodies launching the calculation base by letter. Inevitably, this issue reached the Superior Court of Justice (STJ), and through repetitive appeals, theme 1,113, derived from REsp 1,937,821, was judged in which the market value presented in article 38 of the National Tax Code (CTN) should be interpreted as the value of the property transferred under normal market conditions. However, large municipalities are not applying the precedent, as some are based on the opinion of the Brazilian Association of Capital Finance Secretariats (Abrasf), raising that the Public Administration cannot be bound in decisions on the systematics of repetitive appeals based on article 927 of the Code of Civil Procedure (CPC). This study then sets out to understand the need to reform the CTN to link the Public Administration to the systematic decisions of repetitives. The methodology used consists of bibliographical research, based on books, scientific articles, jurisprudence and norms related to the subject. Thus, it is concluded that the system of repetitive appeals has a binding effect restricted to the Judiciary. It is necessary to issue a normative act, by means of a complementary law, including a new device in the CTN, in order to link the systematic of repetitive resources to the Public Administration.